2021
DOI: 10.7717/peerj.10998
|View full text |Cite
|
Sign up to set email alerts
|

High throughput microRNAs sequencing profile of serum exosomes in women with and without polycystic ovarian syndrome

Abstract: Background Polycystic ovary syndrome (PCOS) is the most common type of endocrine disorder, affecting 5–11% of women of reproductive age worldwide. microRNAs (miRNAs) stably exist in circulating blood encapsulated in extracellular vesicles such as exosomes; therefore, serum miRNAs have the potential to serve as novel PCOS biomarkers. Methods To identify miRNA biomarkers that are associated with PCOS, we performed a comprehensive sequence-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Samples were sieved using 0.22-μm-pore-size filters following a method describedpreviously [ 13 ]. After precipitation of exosomes with the ExoQuick Exosome Precipitation Solution (System Biosciences-SBI), they were analyzed using an electron microscope (FEI Quanta 250, Thermo Fisher Scientific, Eindhoven, the Netherlands), the Nano particle tracking analysis (NTA) (ZetaView PMX 110, Particle Metrix, Meerbusch, Germany), and Western blot analysis (for CD63) were used to characterize isolated exosomes.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were sieved using 0.22-μm-pore-size filters following a method describedpreviously [ 13 ]. After precipitation of exosomes with the ExoQuick Exosome Precipitation Solution (System Biosciences-SBI), they were analyzed using an electron microscope (FEI Quanta 250, Thermo Fisher Scientific, Eindhoven, the Netherlands), the Nano particle tracking analysis (NTA) (ZetaView PMX 110, Particle Metrix, Meerbusch, Germany), and Western blot analysis (for CD63) were used to characterize isolated exosomes.…”
Section: Methodsmentioning
confidence: 99%
“…[74, [90][91][92][93][94] ultimately may lead to an early intervention. Recent studies have found that cargo from follicle-derived exosomes includes various PCOS-specific miRNAs such as miR-373, miR-640, and miR-654-5p, with newer biomarkers being hsa-miR-1299, hsa-miR-6818-5p hsa-miR-192-5p, and hsa-miR-145-5p [66,67]. These specific miRNA biomarkers have been found to be overexpressed in PCOS patients and may possibly be used as diagnostic tools [67].…”
Section: Pre-eclampsiamentioning
confidence: 99%
“…Recent studies have found that cargo from follicle-derived exosomes includes various PCOS-specific miRNAs such as miR-373, miR-640, and miR-654-5p, with newer biomarkers being hsa-miR-1299, hsa-miR-6818-5p hsa-miR-192-5p, and hsa-miR-145-5p [66,67]. These specific miRNA biomarkers have been found to be overexpressed in PCOS patients and may possibly be used as diagnostic tools [67]. Furthermore, another recent study found that serum exosomes from PCOS patients expressed highly elevated levels of miR-590-3p and miR-27a-5p [62].…”
Section: Pre-eclampsiamentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were sieved using 0.22-µm-pore-size lters following a method describedpreviously 14 . After precipitation of exosomes with the ExoQuick Exosome Precipitation Solution (System Biosciences-SBI), they were analyzed using an electron microscope (FEI Quanta 250, Thermo Fisher Scienti c, Eindhoven, the Netherlands), the Nano particle tracking analysis (NTA) (ZetaView PMX 110, Particle Metrix, Meerbusch, Germany), and Western blot analysis (for CD63) were used to characterize isolated exosomes.…”
Section: Exosomes Puri Cation and Characterizationmentioning
confidence: 99%